AVCO Mouthwash - Abllah, Zurainie; Abu Bakar, Mohd Rushdi (IM Books Everything, 2019)
Virgin Cononut Oil (VCO) is well known of its wide benefits to oral and general health. The ayurvedic technique of ‘oil pulling’ has been practice by mostly in India and recently has spread to the world wide. The Activated Virgin Coconut Oil (AVCO) is a modified version of VCO where the effect of free fatty acids inside VCO is fully released thus provides more effective effects to address oral problems. The objective of this invention is to provide a halal, green and non-alcohol mouthwash as an alternative to the conventional one in market. The IP (patent) has been granted and the id number is PT6646/UIAM/18. This invention will benefit the public especially those who looking for the alternative in using mouthwash as this mouthwash offers halal, green and non-alcohol based mouthwash.